Prevalence of Traumatic Dental Injuries among Contact Sport Practitioners in Northeast of Iran in 2012 - Armita Rouhani; Jamileh Ghoddusi; Majid Reza Rahmandost; Majid Akbari (Mashhad University of Medical Sciences, 2016)
Introduction: Contact sports may lead to dental injures, which may often be prevented by using mouthguards. The purpose of this study was to evaluate the prevalence of traumatic dental injuries (TDI) in professional contact sport athletes and to determine the awareness regarding use of mouthguards in this group. Methods: A questionnaire containing a number of  questions regarding the demographic data of participants, experiences of trauma and their behavior after that and use of mouthguard, was distributed amongst 100 contact sport athletes. Results: eighty athletes returned the questionnaire. The age range of most of the participants (44.2%)  was between 20-30  .Also most of them had been practicing in contact sports for 1 to 5 years (37.3%). 26.2% of the athletes had experienced some sort of dental trauma. There was no significant difference between the injuries in males and females (p> 0.05). Luxation injuries were the most common type of TDI (47.7%), followed by crown fractures (42.1%) and avulsion (10.5%). 89.7% of athletes had already been informed about using mouthguards, however only 10.3% reported having used them. Conclusion: According to the results of this study, the rate of TDI among contact sport practitioners in Iran is high; however the use of mouthguards by athletes is low. Dentists and sports authorities should promote the use of mouthguards in contact sports to decreases the risk of dental trauma and tooth loss.